EVALUATION OF THE INTEGRATED MULTICRITERIAL AIRCRAFT LOAD OPTIMIZATION MODEL - Sahun, Yelizaveta (Proceedings of National Aviation University (archive), 2020)
Purpose: presenting of results evaluation after implementation of the new developed load optimization model and model adequacy analysis in order to prove the efficiency by reducing of the main loading time criteria. Methods: experiment, heuristics, statistics, imitation modeling. Results: the developed load optimization model passed all verification procedures and the experimental data analysis enhanced its relevance in an aircraft load optimization process. Discussion: Some parametric statistical adequacy criteria were analyzed to point, that the aircraft load optimization model cannot be checked with their help. Thus, an optimization model with time criteria can be analyzed for adequacy with non – parametric T- Wilcoxon criteria. The article presents the experimental data research that demonstrates the difference between model parameters and real duration of loading / unloading procedures in real time conditions. The imitation model shows the minimization of an aircraft loading time after model’s implementation. So, the following verification results can be considered as a final part of the integrated multicriterial load optimization model’s effectiveness.